Optimization Method to Determine the Kinetic Rate Constants for the Removal of Benzo[a]pyrene and Anthracene in Water through the Fenton Process (2022)
ABSTRACT: The reaction rate constants concerning the removal of benzo[a]pyrene (BaP) and anthracene (AN) in water by the Fenton process can be commonly found from the experimental data and by using regression models. However, this calculation is time-consuming and a difficult task. Therefore, an algorithm for the determination of the rate constant depletion of the pollutants of interest should be developed. In this study, several algorithms were developed, using MATLAB® software for representing AN and BaP elimination by the Fenton process under an experimental domain. These algorithms were derived from the first-, second- and third-order kinetic models, as well as from the double exponential and the Behnajady-Modir Shahla-Ghanbari (BMG) kinetic models. Regarding the AN and BaP removal kinetics, the double exponential and the BMG models were found to exhibit the highest correlation coefficients (>0.98 and >0.95, respectively) in comparison with those ones obtained from the first-, second- and third-order kinetic models (>0.80, >0.85 and >0.88, respectively). It was found that the algorithms can be used to optimize and fit the rate constants by creating an objective function that fits and represents the experimental data obtained concerning the removal of the compounds of interest through the Fenton advanced oxidation process.